2018
DOI: 10.1002/smll.201703818
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich‐like MoS2@SnO2@C with High Capacity and Stability for Sodium/Potassium Ion Batteries

Abstract: Sandwich-like MoS @SnO @C nanosheets are prepared by facile hydrothermal reactions. SnO nanosheets can attach to exfoliated MoS nanosheets to prevent restacking of adjacent MoS nanosheets, and carbon transformed from polyvinylpyrrolidone is coated on MoS @SnO , forming a sandwich structure to maintain cycling stability. As an anode for sodium-ion batteries, the electrode greatly deliverers a high initial discharge specific capacity of 530 mA h g and maintains at 396 mA h g after 150 cycles at 0.1 A g . Even at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 58 publications
5
87
0
Order By: Relevance
“…It is known that the low‐voltage (<0.50 V) capacity contribution of anode is more essential to the energy density of the full cells . Comparing with the previously reported PIB anodes in ester‐based electrolytes such as carbon‐based materials, conversion‐based materials, and alloy‐based materials, the as‐prepared SnS 2 @rGO‐2 electrode delivers the highest reversible capacity in the low voltage range of 0.01–0.50 V (Figure c). Therefore, this encouraging result suggests that SnS 2 @rGO‐2 possesses great potential as high‐energy‐density anode material for PIBs.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…It is known that the low‐voltage (<0.50 V) capacity contribution of anode is more essential to the energy density of the full cells . Comparing with the previously reported PIB anodes in ester‐based electrolytes such as carbon‐based materials, conversion‐based materials, and alloy‐based materials, the as‐prepared SnS 2 @rGO‐2 electrode delivers the highest reversible capacity in the low voltage range of 0.01–0.50 V (Figure c). Therefore, this encouraging result suggests that SnS 2 @rGO‐2 possesses great potential as high‐energy‐density anode material for PIBs.…”
Section: Resultsmentioning
confidence: 77%
“…However, their low specific capacity (around 200 mAh g −1 ) and high average operating voltage (>0.5 V) limit the energy density of PIBs . Very recently, some noncarbonaceous anodes based on conversion/alloying mechanisms have been explored for K storage, exhibiting increased specific capacity compared with the carbonaceous materials . Among them, Sn‐based compounds (e.g., Sn 4 P 3 , SnS 2 ) combining the conversion and alloying reactions are expected to be promising anode candidates due to their high theoretical specific capacities .…”
Section: Introductionmentioning
confidence: 99%
“…For MoS 2 @C composite, all the diffraction peaks can be matched with hexagonal MoS 2 phase (JCPDS No. 17‐1492), and the diffraction peaks of carbon layer cannot be observed due to the low content of amorphous carbon ,,. After second hydrothermal treatment, the main diffraction peaks located at 13.4°, 33.0°, 39.7°and 58.5° can be indexed to the (002), (100), (103) and (110) planes of hexagonal MoS 2 phase (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…illustrated how doped MoS 2 breaks in transition‐metal influence the CO 2 electrochemical reduction by theoretical calculation. Chen et al. investigated the electrocatalytic activity of sandwich‐like MoS 2 @SnO 2 @C as an anode for sodium‐ion batteries, the results indicated that the capacitance is beyond imagination reached up to 530 mA h g −1 .…”
Section: Introductionmentioning
confidence: 99%